Histopathological and morphological alterations caused by plasmodiophora brassicae in brassica oleracea l. (2011)
Plasmodiophora brassicae is a plant pathogen of the Brassicaceae family, which presents a remarkable ability to survive in soil and high capacity of infection, significantly reducing crop yields. The present histopathologycal study conducted with the aim of contributing to knowledge of the infection cycle of the pathogen, showed the presence of multinucleated plasmodia at cortex and periderm cells level in infected cabbage roots, as well as thickening and disruption of cell wall. As a result of this disarray was observed in diseased tissues, mainly in the cortex, compared with healthy tissues in uninfected plants. The inoculation cabbage seedlings with dormant spores of P. brassicae at concentrations of 1 ∙ 107 and 1 ∙ 108 spores mL-1 by immersion and spray, induced a higher growth and less growth longitudinal lateral roots compared with uninoculated plants as well as presence of young plasmodia at 28 days after inoculation.